Socio-Emotional Competencies in Primary School Through A Social Constructivist Approach - Alexander, Quintero Camacho, Carlos (Journal of Ecohumanism, 2025)
Theme: The social constructivist approach allows to establish processes of transformation in the educational field, guiding the motivated participation of the teacher and the concentration of efforts to promote socio-emotional competencies. Objectives: This article, derived from the doctoral research process, had as its general objective: To interpret the different pedagogical conceptions on the development of socio-emotional competencies guided through teaching under a social constructivist approach applicable in basic primary education. Therefore, the specific objectives were: 1. To identify the different pedagogical conceptions of the teacher on teaching with a social constructivist approach in basic primary education of the public educational institution. 2. To describe the pedagogical experiences on the development of socio-emotional competencies in basic primary education in public educational institutions. Method: maintains a qualitative approach, under the socio-critical paradigm, using hermeneutical phenomenology as a method based on the case study, in which six moments or phases were followed. The participants were ten teachers linked to the Luis Carlos Galán Educational Institution in the municipality of Villa Garzón de Putumayo, to whom inclusion and exclusion criteria were applied, as well as informed consent. The collection instruments were the focus group and semi-structured interview scripts, validated through expert judgment. Conclusion: Social constructivism as a support approach for the development of socio-emotional competencies implies highlighting the importance of social contact and the relevance of the learning context, showing the need to address the processes of social interaction.